Οι μακεδονικοί οικισμοί σε μια πρόθεση της μονής του Σπαρμού (1602-1674) - Σπανός, Βασίλης Κ. (Μακεδονικά, 2011)
The script number 84 of the Monastery of Olympiotissa is one of thethree known «prothesis» of the Monastery Sparmos, which was built at thesouthwest side of mount Olympus before 1600. This «prothesis» contains allthe names of those who gave their contributions to the monastery.The registration began in 1602, when most names of the contributorswere written down and it was completed on the 26th of July 1674. There is atotal number of twenty macedonian settlements mentioned there, and theauthor of this codex identified all those which could be identified in the firstpart of this scholarly work. In the second part of his work there are 46classified names which include 92 men contributors and 32 other names with42 women contributors belonging to the first part of the «prothesis» (1602).There are also 36 surnames of 132 contributors of the same year.Finally the leaves 23 to 26 of the above mentioned «prothesis» are now published.